Family history of cancer Filipino first-degree relatives' perspectives on disease and inherited gene risks - Amoranto, Abegail Jayne (2017)
Family history plays an important role in cancer risk assessment and management as it reflects the contribution of inherited genes, shared lifestyle and environmental factors in the development of disease in the family. An individual's understanding of family history influences perceptions of cancer risks and control, which consequently affect adoption of health behaviors and screening practices. However, discrepancies may exist between the ways lay people and health professionals perceive family history, hindering effective use of family history in cancer risk communication and promotion of health behaviors. This study aimed to address this gap and explore lay constructs of family history of cancer in relation to perceptions of disease causation and inheritance of genes, perceived risk, and risk management among Filipino first-degree relatives (FDRs) of cancer patients. Employing a qualitative descriptive research design, the investigators also identified variations in meanings of family history between siblings and children of affected relatives, and between Filipinos with first-degree relatives diagnosed with onset cancer from those with relatives who developed cancer at typical ages. A purposive sample of seventeen (17) individuals, who are siblings of offspring of patients diagnosed with colorectal cancer at the University of the Philippines-Philippine General Hospital were interviewed. Qualitative content analysis (QCA) and continuous cooperative analysis (CCA) were employed to identify and compare themes and patterns in the interviews. The findings of the study confirm the constructs of the Model of Familial Risk Perception. Perceived familial and personal risk are significantly influenced by the individual's understanding of their family history of disease, disease inheritance, and perceived control. One new finding is the presence of two opposite definitions of "family history" among Filipino first-degree relatives, which affect how they recognize and classify their familial risk of developing the disease. These variations in meanings and understanding of family history have been found to influence participants' understanding of their familial risks and personal sense of vulnerability. The study highlights potential differences between the way Filipino FDRs and clinicians determine and understand familial risk of cancer, and points out the need for exploration of these discrepancies for a more effective risk communication.